STUDY OF THE INFLUENCE OF THE GEOMETRIC PARAMETERS OF THE LAVAL NOZZLE ON THE GAS FLOW TEMPERATURE CHANGE - Liakh М. М.; Mykhailiuk, V. V.; Yatsyshyn Т. М.; Vytrykhovskyi Y. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
The Laval nozzle was widely used in various branches of the national economy: mechanical engineering, chemical and petrochemical industry, military, etc. The gas flow passing through the Laval nozzle changes its characteristics, namely when the gas flow velocity reaches the speed of sound, the temperature and pressure drop at the exit from the nozzle. This phenomenon can be used to cool the gas flow. However, in the traditional Laval nozzle design, the zone where the lowest temperature is observed is small. In this article, a study of the influence of the geometrical parameters of the Laval nozzle on the change in the temperature of the gas flow is carried out. For the study, 12 different designs of nozzles were built, having the same basic dimensions: diameter of the inner hole, inlet and outlet diameters, length of the nozzle. The environment and boundary conditions used during the simulation were assumed to be the same for all nozzles. As a result, distributions of the temperature of the environment in the cross section for all the studied nozzle designs were obtained. Analyzing the results of the simulation, it was found that in all nozzle designs there is a decrease in temperature approximately from 100 0C to 60 0C. However, the zones in which the maximum decrease in temperature is observed are quite small. After the zones with the lowest temperatures in the studied nozzle designs, there are zones of increased temperature (in the range of 70-80 0C), which are significantly larger than the zones with the minimum temperature. Then, in the next zone, a subsequent increase in temperature occurs. Also, on the basis of the simulation results, nozzle designs were selected, which will be further investigated and improved. It is planned to carry out simulated painting of nozzles, where the main attention will be focused on such a parameter as the Mach number, its effect on the temperature change and its distribution along the length of the three-dimensional model structure.